GURU DALAM DIMENSI PEMBELAJARAN - ., Suraga (Universitas Islam Negeri Alauddin Makassar, 2020)
The presence of a teacher in the learning dimension is like a lantern for students. teachers as agents of renewal, teachers can be role models for students and the surrounding environment wherever they are, especially in learning, teachers can also teach many things to students from not knowing to knowing so that it is useful for the nation and state. So it is important for us to understand the position of the teacher in learning. If the teacher, students are at least able to learn knowledge and strengthen attitudes or morals. This, in line with the formation of noble morals, is a goal that should be prioritized in education, regardless of the material being taught. Therefore, every teacher is required to be able to explain the spirit or ethical values contained in any material taught, especially through attitudes and exemplary, thus, students or learners are not only given concepts that are purely scientific in nature, but also obtain a mirror and inculcate ethical values in it